Entrepreneurial Leadership through Innovation Capacity as an Effort to Increase Competitive Advantage of UMKM in Era of Asean Economic Community (MEA) (Micro Business Study in Kabupaten Bangka) - Maya Yusnita; Nanang Wahyudin (Fakultas Ekonomi, Universitas Bangka Belitung, 2017)
According to data compiled by the World Economic Forum, Indonesia's competitiveness is still below the competitiveness of other ASEAN countries such as Singapore, Malaysia, Brunei Darussalam and Thailand. The cause is the indication of the relatively low level of innovation. Increased innovation is determined by the human resources owned by the organization. Innovation is an output from organizations that utilize input resources in the form of knowledge (knowledge), information and experience. Therefore, the key to success of an innovation lies in the knowledge and quality of human resources. Human resources here can not be separated from how the leadership of an entrepreneur in managing the business they digelutinya, so have a competitive advantage, especially in the era of the ASEAN Economic Community (MEA) today. The purpose of this study is to know and analyze: (1) the influence of entrepreneurial leadership on innovation capacity, (2) the effect of innovation capacity on competitive advantage, and how (3) the influence of entrepreneurial leadership on competitive advantage. The research respondents are 60 micro business actors in Bangka Regency spread over 5 districts, including Merawang, Mendo Barat, Puding Besar, Sungailiat and Belinyu. Collected data is processed by path analysis method (path analysis). The results showed that the entrepreneurial leadership variables influenced the capacity of innovation, as well as the variable capacity of innovation and entrepreneurial leadership variables also had an influence on competitive advantage in micro business in Bangka Regency.